SISTEM LELANG KOMODITAS CABAI MERAH DI PASAR LELANG DESA MUARA BURNAI I KECAMATAN LEMPUING JAYA KABUPATEN OGAN KOMERING ILIR (Societa: Jurnal Ilmu-Ilmu Agribisnis, 2022)
ABSTRACTThis study aims to determine the chili auction system in the auction market of Muara Burnai I Village, Lempuing Jaya District. to find out the benefits felt by chili farmers with the existence of an auction market in Muara Burnai I Village, Lempuing Jaya District and to find out the income of farmers who sell chilies with an auction system in Muara Burnai I Village, Lempuing Jaya District. This research was conducted in Muara Burnai I Village, Lempuing Jaya District, Ogan Komering Ilir Regency in August-October 2021. The research method used is a survey method. While the sampling method usedin this research is purposive sampling method and simple random sampling (simple random). The method of data processing and data analysis used is descriptive qualitative analysis. The results of this study note that the chili commodity auction system at the Auction Market of Muara Burnai I Village uses a closed auction system with prices sent via cellular short message (SMS) and the auction process is carried out four times a week, and in payment transactions in the auction market there is a discount for farmers of Rp. 500/Kg, for cash. The benefits felt by farmers with the existence of an auction market are the ease of marketing chili, high selling prices and being able to borrow capital and agricultural facilities, these benefits can have a good impact in increasing income for farmers. The benefits felt by farmers with the existence of an auction market are the ease of marketing chili, high selling prices and being able to borrow capital and agricultural facilities, these benefits can have a good impact in increasing income for farmers. The income received by farmers from the remaining sales using an auction system at the auction market of Muara Burnai I Village, Lempuing Jaya District, per planting season is Rp. 43,949.016.ABSTRAKPenelitian ini bertujuan untuk mengetahui sistem lelang komoditas cabai di pasar lelang Desa Muara Burnai I Kecamatan Lempuing Jaya, untuk mengetahui manfaat yang dirasakan petani cabai dengan adanya pasar lelang di Desa Muara Burnai I Kecamatan Lempuing Jaya dan untuk mengetahui pendapatan petani yang menjual cabai dengan sistem lelang di Desa Muara Burnai I Kecamatan Lempuing Jaya. Penelitian ini dilaksanakan di Desa Muara Burnai I Kecamatan Lempuing Jaya Kabupaten Ogan Komering Ilir pada bulan Agustus-Oktober 2021. Metode penelitian yang digunakan adalah metode survey. Sedangkan metode penarikan contoh digunakan dalam penelitian ini adalah metode purposive sampling dan simple random sampling (acak sederhana). Metode pengolahan data dan analisis data yang digunakan adalah analisis deskriptif kualitatif. Hasil penelitian ini diketahui bahwa Sistem lelang komoditas cabai di Pasar Lelang Desa Muara Burnai I  menggunakan sistem lelang tertutup dengan harga yang dikirimkan melalui pesan singkat seluler (SMS) Dan Proses pelelangan dilakukan empat kali dalam seminggu, Dan dalam transaksi pembayaran di pasar lelang ini terdapat potongan bagi petani sebesar Rp. 500/Kg, untuk kas. Manfaat yang dirasakan petani dengan adanya pasar lelang adalah kemudahan dalam pemasaran cabai, harga jual tinggi serta bisa meminjam modal dan sarana pertanian, manfaat tersebut bisa memberikan dampak yang baik dalam meningkatan pendapatan bagi petani. Pendapatan yang diterima petani dari sisa penjualan dengan sistem lelang di pasar lelang Desa Muara Burnai I Kecamatan Lempuing Jaya permusim tanam rata-rata sebesar Rp. 43.949.016